(untitled) (CAHIERS MAGELLANES-NS, 2024)
This is a systematic narrative review seeking to understand the impact of trauma across the time of primary dentition development on those of permanent teeth, which is of particular interest in the field of pediatrics. Injury to primary teeth which often occurs during childhood has been identified to cause developmental abnormalities in the succeeding permanent teeth that is enamel hypoplasia, discolouration, late emergence and even crowding. The review is informative, and summarises a pool of studies, while stressing on the necessity of early detection of CADCH and timely intervention to prevent or reduce such adverse effects. New technologies in diagnostics like CBCT and new treatment approaches, like biomaterials and regenerative medicine, have improved the opportunity for the dental professional to treat these individuals adequately. The review also describes the major benefits of early intervention to enhance better long-term oral health outcomes; this is also highly underlined the critical importance of additional studies to fill existing knowledge gaps and develop better-intervention strategies. It is in relation to the focus of this review and its focus on primary dentition trauma and the developmental stage of the permanent teeth that the importance of early prevention and management of dental injuries is underlined. It is evident from the study that the shifting technology, together with the knowledge of developmental effects of dental trauma can facilitate better management of patient care in the paediatric dental practice.